2021
DOI: 10.5114/amsad.2021.105255
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, diabetes mellitus, and cerebrovascular disease predispose to a more severe outcome of COVID-19

Abstract: Introduction The world is currently facing the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The total number of cases of coronavirus disease 2019 (COVID-19) is rising daily and no vaccine has yet been approved. While the pathophysiology behind the virus is still being studied, many possible several risk factors using small sample sizes have been found. Material and methods We conducted a pooled analysis using several databases such as Medlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 116 publications
2
11
0
Order By: Relevance
“…This study reported similar results with previous studies, that COVID-19 patients with diabetes mellitus had higher risk of in-hospital mortality than those without diabetes mellitus [ 5 , 6 , 7 , 8 , 23 , 25 , 26 , 27 , 28 , 29 ]. This result could be explained by chronic inflammatory conditions occurring among COVID-19 patients with DM.…”
Section: Discussionsupporting
confidence: 91%
“…This study reported similar results with previous studies, that COVID-19 patients with diabetes mellitus had higher risk of in-hospital mortality than those without diabetes mellitus [ 5 , 6 , 7 , 8 , 23 , 25 , 26 , 27 , 28 , 29 ]. This result could be explained by chronic inflammatory conditions occurring among COVID-19 patients with DM.…”
Section: Discussionsupporting
confidence: 91%
“…( 16) Furthermore, we also linked chronic pulmonary disease, obesity, diabetes, alcohol abuse, hypertension, dialysis use, chronic kidney disease, and presence of an old MI to poorer outcomes among MS patients, as already reported in the general population. (17)(18)(19)(20)(21)(22)(23)(24)(25) Finally, our study reported racial disparities as Blacks with MS admitted for COVID-19 had lower odds of death than Whites, while Hispanics showed increased risk. This contradicts past results from Salter et al based on the North American Registry, whereby the mortality rate among Whites with MS and COVID-positive was estimated at 3.5%, while it was 4.2% among Blacks, and 1.1% among Hispanics.…”
Section: Discussionmentioning
confidence: 48%
“…However, there was no difference in the incidence of adverse reactions among the different grades of risk after the first or second doses. Hypertension, diabetes mellitus, and cerebrovascular disease have been reported to predispose patients to a more severe outcome of COVID-19 ( 26 ). However, the adverse reactions of the COVID-19 vaccine (mainly inactivated vaccine) did not increase with an increase in stroke risk factors.…”
Section: Discussionmentioning
confidence: 99%